Registration of Four Winter‐Hardy Faba Bean Germplasm Lines for Use in Winter Pulse and Cover Crop Development. Issue 3 (21st August 2015) - Landry, Erik J.; Lafferty, Jolene E.; Coyne, Clarice J.; Pan, William L.; Hu, Jinguo
Abstract : Faba bean ( Vicia faba L.) is a versatile crop grown for food, feed, vegetable, or cover crop purposes in many countries. In response to the growing demand for winter annual legumes for cover crop development in the United States, we developed four winter‐hardy faba bean germplasm lines, WH‐1 (Reg. No. GP‐3, PI 674326), WH‐2 (Reg. No. GP‐4, PI 674327), WH‐3 (Reg. No. GP‐5, PI 674328), and WH‐4 (Reg. No. GP‐6, PI 674329) at the USDA‐ARS, Western Regional Plant Introduction Station, Pullman, WA, after six consecutive seasons of overwintering selection at three farms in two locations; Pullman and Central Ferry, WA. These four accessions were identified after the initial screening of 175 accessions from the USDA faba bean germplasm during the 2008–2009 and 2009–2010 winter seasons. In the following years, these populations were compared with several winter‐type cultivars and breeding lines from Europe. During the final testing season, in 2013–2014, selected and original accessions were compared. The average increase in percentage survival was 84% across the four accessions. Furthermore, the winter hardiness of the selected accessions was comparable to European materials. These four lines are potential reservoirs of useful diversity accessible for the development of a winter annual legume cover crop in the U.S. Pacific Northwest and other regions up to USDA plant hardiness zone 6b.